Solid waste management in western Canadian First Nations. (15th June 2021) - Assuah, Anderson; Sinclair, A.J.
Highlights: Diverse funding sources are needed to expand infrastructure and sustain programs. Enforcement of solid waste bylaws and regulation are lacking in communities. Some First Nations communities are not aware of provincial stewardship programs. Improved solid waste infrastructure has led to establishing diversion programs. Communities are providing curbside pickup for waste similar to municipalities. Abstract: This research examined solid waste management on First Nations communities in western Canada to provide information and insight into programs, practices, policies, and activities, as well as to help bridge an identified gap related to these in the literature. Utilizing a qualitative case study approach, we examined twelve First Nations communities in Canada's western provinces, which relative to other communities, had 'advanced' solid waste management systems in place. Interviews conducted in each of the communities yielded information on six themes grounded in the data, including solid waste facilities and infrastructure, solid waste programs, local capacity, provincial stewardship programs, regulation and enforcement, and funding/finance. Our analysis show that majority of the communities examined are advancing their waste management systems and now have infrastructure/facilities, such as transfer stations and recycling depots, and have implemented recycling programs, which they previously did not have. As well, we learned that implementing such programs has reduced practices, such as open dumping, which the literature highlights as a common way of managing waste in First Nations communities. Most of the communities attributed the success of their programs to regular residential curbside pickups, ability to transport waste out of the community, and community involvement and interest in programs. Despite these improvements, inadequate funding hampers the efforts of communities to sustain and/or expand their programs and maintain facilities. Additionally, most communities face challenges partnering with provincial stewardship programs, and some communities are not clear whether they even qualify to participate in these programs.